KONTRIBUSI HUKUM ISLAM TERHADAP PENGUATAN HAK ASASI MANUSIA DI INDONESIA - Syuaib Jailuddin; Mahfuz Assiddiq; Kurniati; A. Qadir Gassing (IAIN Ambon, 2026)
Human Rights (HAM) are fundamental rights inherent in every human being from birth and guaranteed by national law and religious principles. In the context of Indonesia, where the majority of the population is Muslim, studying the relationship between Islamic law and human rights is crucial to understanding the intersection between the two. Islamic law places human dignity as a primary value through the principle of al-ḍarūriyyāt al-khamsah, which means safeguarding religion, life, intellect, lineage, and property. This principle aligns with the objectives of human rights, which emphasize the protection and respect of human dignity. Through the concept of Maqāṣid al-Syarī'ah, Islamic law aims to realize public welfare and prevent harm, thus making a real contribution to the implementation of human rights, both in social life and in the national legal system. In Indonesia, the influence of Islamic law is evident in the formation of legislation that aligns with the divine values of Pancasila. This demonstrates that Islamic law can serve as a moral and ethical basis for strengthening human rights, thereby creating a just and harmonious society. Keywords: islamic law, human rights, maqāṣid al-syarī'ah